ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG PASAR TERUBUK KABUPATEN BENGKALIS - Nurul Huda; Dedi Ismawardi (Bertuah: Journal of Sharia and Islamic Economics, 2020)
The purpose of this research is to determine the effect of capital, working hours and location on the income of marketeer in Terubuk market, Bengkalis Regency either partially or simultaneously. The results of this study indicate that capital has a significant effect on the income of market marketeers with tcount = 2.310> 1.998 = ttable, and sig = 0.024 <0.05. Working hours have a significant effect on the income of market marketeers with tcount = 2.261> 1.998 = ttable, and sig = 0.027 <0.05. Location has a significant effect on market marketeer's income with tcount = 3.391> 1.998 = ttable, and sig = 0.000 <0.05. And simultaneously capital, working hours and location have a positive and significant effect on the income of market marketeers with a value of F = 68.842> 2.76 (F0.025 (3:67) = 2.76) and sig = 0.000 <0.05. The conclusions from the results of this study indicate that capital, working hours and location partially and simultaneously have a positive and significant  market marketeer in Terubuk, Bengkalis Regency. Keywords: Capital, Working Hours, Location, Income and Terubuk Market.